Characterisation of Staphylococcus aureus Strains and Their Prophages That Carry Horse-Specific Leukocidin Genes lukP/Q - Stefan Monecke; Sindy Burgold-Voigt; Andrea T. Feßler; Martina Krapf; Igor Loncaric; Elisabeth M. Liebler-Tenorio; Sascha D. Braun; Celia Diezel; Elke Müller; Martin Reinicke; Annett Reissig; Adriana Cabal Rosel; et al. (Toxins, 2025)
Leukocidins of Staphylococcus (S.) aureus are bicomponent toxins that form polymeric pores in host leukocyte membranes, leading to cell death and/or triggering apoptosis. Some of these toxin genes are located on prophages and are associated with specific hosts. The genes lukP/Q have been described from equine S. aureus isolates. We examined the genomes, including the lukP/Q prophages, of S. aureus strains belonging to clonal complexes CC1, CC350, CC816, and CC8115. In addition to sequencing, phages were characterised by mitomycin C induction and transmission electron microscopy (TEM). All lukP/Q prophages integrated into the lip2=geh gene, and all included also the gene scn-eq encoding an equine staphylococcal complement inhibitor. The lukP/Q prophages clustered, based on gene content and allelic variants, into three groups. One was found in CC1 and CC97 sequences; one was present mainly in CC350 but also in other lineages (CC1, CC97, CC133, CC398); and a third one was exclusively observed in CC816 and CC8115. Prophages of the latter group additionally included a rare enterotoxin A allele (sea320E). Moreover, a prophage from a CC522 goat isolate was found to harbour lukP. Its lukF component could be regarded as chimaera comprising parts of lukQ and of lukF-P83. A putative kinase gene of 1095 basepairs was found to be associated with equine strains of S. aureus. It was also localised on prophages. However, these prophages were different from the ones that carried lukP/Q, and three different integration sites of kinase-carrying phages were identified. These observations confirmed the presence of prophage-located important virulence-associated genes in equine S. aureus and that certain prophages might determine the host specificity of the staphylococcal strains they reside in.